Citrus Extract as a Perspective for the Control of Dyslipidemia: A Systematic Review With Meta-Analysis From Animal Models to Human Studies - Carvalho, Betina M. R.; Nascimento, Laranda C.; Nascimento, Jessica C.; Gonçalves, Vitória S. dos S.; Ziegelmann, Patricia K.; Tavares, Débora S.; Guimarães, Adriana G. (Frontiers in Pharmacology, 2022)
This study aims to obtain scientific evidence on the use of Citrus to control dyslipidemia. The surveys were carried out in 2020 and updated in March 2021, in the Pubmed, Scopus, Lilacs and Scielo databases, using the descriptors: Citrus, dyslipidemias, hypercholesterolemia, hyperlipidemias, lipoproteins and cholesterol. The risk of bias was assessed according to the Cochrane methodology for clinical trials and ARRIVE for pre-clinical trials. A meta-analysis was performed using the software R application. A total of 958 articles were identified and 26 studies demonstrating the effectiveness of the Citrus genus in controlling dyslipidemia were selected, of which 25 were included in the meta-analysis. The effects of Citrus products on dyslipidemia appear consistently robust, acting to reduce total cholesterol, LDL and triglycerides, in addition to increasing HDL. These effects are associated with the composition of the extracts, extremely rich in antioxidant, as flavonoids, and that act on biochemical targets involved in lipogenesis and beta-oxidation. The risk of bias over all of the included studies was considered critically low to moderate. The meta-analysis demonstrated results favorable to control dyslipidemia by Citrus products. On the other hand, high heterogeneity values were identified, weakening the evidence presented. From this study, tone can suggest that Citrus species extracts are potential candidates for dyslipidemia control, but more studies are needed to increase the strength of this occurrence. Registered with PROSPERO: CRD42019121238.